Advancing Healthy Food Service in the United States: State Food Service Guidelines Policy Adoption and Implementation Supports, 2015-2019. Issue 3 (March 2023) - Lowry-Warnock, Amy; Strombom, Nicole; Mugavero, Kristy; Harris, Diane; Blanck, Heidi M.; Onufrak, Stephen
Purpose: Food service guidelines (FSG) policies can impact the nutritional quality of millions of meals sold or served to government employees, citizens in public places, or institutionalized persons. This study examines state FSG policies adopted January 1, 2015 to April 1, 2019, and uses a FSG Classification Tool (FSG Tool) to quantify alignment with nutrition recommendations for public health impact. Design: Quantitative Content Analysis Setting: State Government Worksites and Facilities Participants: 50 states and District of Columbia (D.C.) in the United States. Measures: Frequency of policies and percent alignment to FSG tool. Analysis: FSG policies were identified using legal databases to assess state statutes, regulations, and executive orders. Content analysis and coding determined attributes of policies across 4 FSG Tool domains, (1) nutrition standards referenced; (2) behavioral design strategies encouraging selection of healthier offerings; (3) facility efficiency and environmental sustainability; and (4) FSG implementation supports. Results: From 2015-2019, 5 FSG policies met study inclusion criteria. Four out of 5 policies earned a perfect nutrition score (100%) by referencing nutrition standards that align with the Dietary Guidelines for Americans (DGA) and are operationalized for use in food service venues. Four out of 5 policies included at least 1 implementation supports provision, such as naming an implementing agency, and 2 included provisions that encourage local food sourcing. Conclusion: From 2015-2019, overall FSG policy comprehensiveness scores ranged from 24% to 73%, with most policies referencing food and nutrition standards that align to national nutrition recommendations. Public health practitioners can educate decision makers on the potential impact of FSG policies on diet-related health outcomes and associated cost savings, as well as other important co-benefits that support locally grown products and environmental sustainability practices.